Psychometric Evaluation and Establishing Norms of Croatian SF-36 Health Survey: Framework for Subjective Health Research - Maslić Seršić, Darja (Array, 2006)
Aim: To evaluate metric characteristics, as well as to provide population norms for the Croatian version of a well known international instrument assessing subjective health – SF-36 Health Survey. Method: The questionnaire was administered to a representative sample of Croatian adult population (n=9, 070) and three standard techniques were used in data analysis: reliability tests, descriptive statistics, and factor analysis. We presented population norms in two standard forms – the SF-36 Health Profile and percentile values for different age groups of men and women. Results: The Croatian version of the SF-36R had generally acceptable metric characteristics including its construct validity - internal consistency of the scales ranged from 0.78 to 0.94 ; psychological health and physical health were extracted as two latent dimensions which explained 72.4% of the score variance. Somewhat less favorable results were obtained concerning its discriminative validity. All SF-36 scales showed negative asymmetry of score distributions, and some had high floor and ceiling effects – skewness estimations ranged from -0.12 to -0.91, with the highest floor effect of 30% and ceiling effect of 63%. Conclusion: Presented population norms for the Croatian version of SF-36 Health survey could be used in future research as a frame for comparisons across disease and condition groups in searching for better information about what works best in health care.